2015
DOI: 10.1039/c5ja00105f
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of inorganic arsenic in particulate matter by combining HPLC/ICP-MS and XANES analyses

Abstract: Inorganic arsenic species in ambient particulate matter (PM 10 and PM 2.5 ) have been determined in an urban area, in the vicinity of a metallurgical industrial plant. The developed high performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC/ICP-MS) method allows monitoring of particulate As(III) and As(V)-species, with a limit of quantification of 0.34 ng m À3 As(III) and 0.23 ng m À3 As(V), respectively. Good agreement was obtained between the sum of the concentrations of As(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Bulk chemical analysis was carried out on the ground 63 mm fraction by ICP-OES aer lithium metaborate/ tetraborate fusion, and the composition of the near-surface region (2-10 nm) was determined XPS. 84 The HPLC-ICP-MS method offered a LOQ of 0.34 ng m À3 for As III and 0.23 ng m À3 for As V . The As compounds were found to be concentrated onto the ash surface in the form of As III -S and As V -O species.…”
Section: Arsenicmentioning
confidence: 99%
“…Bulk chemical analysis was carried out on the ground 63 mm fraction by ICP-OES aer lithium metaborate/ tetraborate fusion, and the composition of the near-surface region (2-10 nm) was determined XPS. 84 The HPLC-ICP-MS method offered a LOQ of 0.34 ng m À3 for As III and 0.23 ng m À3 for As V . The As compounds were found to be concentrated onto the ash surface in the form of As III -S and As V -O species.…”
Section: Arsenicmentioning
confidence: 99%
“…), concentrations of As (and their species) are shaped mainly by municipal emission or time-stable road traffic emissions [14]. X-ray analysis of PM from industrial area showed that As bound to PM occurs as: Ca 3 Sr 2 (AsO 4 )2.5(PO4)0.5(OH), As 2 O 3 and As 2 O 5 [15]. Analysis of PM has revealed that inorganic arsenic species, in particular As(V), is the predominant species in atmospheric PM [2016].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of PM has revealed that inorganic arsenic species, in particular As(V), is the predominant species in atmospheric PM [2016]. Their ambient concentrations are higher in PM from industrial areas than in PM from semi-urban sites [14][15][16][17]. For example, high concentrations of PM2.5-bound As (6.4 ng/m 3 for total As, 0.9 ng/m3 for As(III) and 5.5 ng/m 3 for As(V)) were noted in area close to Spain cooper smelter [17].…”
Section: Introductionmentioning
confidence: 99%
“…Speciation of PMbound Cr and As in size-segregated samples has been studied only to a little extent. Inorganic arsenic species were determined for example in PM2.5-10 and PM2.5 in Tapada and Sines in Portugal [27], in PM10 and PM2.5 in Huelva in Spain [28], in Antwerp in Belgium [10] in PM2.5 and PM1 in Zabrze, Poland [29]. These studies indicate the presence of As(V) as the dominating specie in the PM samples, followed by As(III); only Tirez and coworkers [10] showed that the dominant specie in PM2.5 was As(III).…”
Section: Application Of Chromium and Arsenic Speciation Analyses In Pmentioning
confidence: 99%
“…The compounds of Cr and As in PM as well as the shares of its particular species are shaped by emission sources. X-ray analysis of PM collected in industrial area showed that arsenic is present as: Ca3Sr2(AsO4)2.5(PO4)0.5(OH), As2O3 and As2O5 [10] and chromium is present in the chemical forms: Cr2O3, Cr-Fe spinel, Cr(OH)3, Cr(NO3)3, Cr2(SO4)3, and CrCl3. Most of them are not soluble in water in contrary to Cr(VI) compounds, which are water-soluble unless existing as PbCrO4, BaCrO4 and ZnCrO4 (emitted during utilization of chromate pigments and dyes).…”
Section: Introductionmentioning
confidence: 99%